Common Low-Density Lipoprotein Receptor p.G116S Variant Has a Large Effect on Plasma Low-Density Lipoprotein Cholesterol in Circumpolar Inuit Populations. (February 2015) - Dubé, Joseph B.; Wang, Jian; Cao, Henian; McIntyre, Adam D.; Johansen, Christopher T.; Hopkins, Scarlett E.; Stringer, Randa; Hosseinzadeh, Siyavash; Kennedy, Brooke A.; Ban, Matthew R.; Young, T. Kue; Connelly, Philip W.; et al.
Abstract : Background—: Inuit are considered to be vulnerable to cardiovascular disease because their lifestyles are becoming more Westernized. During sequence analysis of Inuit individuals at extremes of lipid traits, we identified 2 nonsynonymous variants in low-density lipoprotein receptor ( LDLR ), namely p.G116S and p.R730W. Methods and Results—: Genotyping these variants in 3324 Inuit from Alaska, Canada, and Greenland showed they were common, with allele frequencies 10% to 15%. Only p.G116S was associated with dyslipidemia: the increase in LDL cholesterol was 0.54 mmol/L (20.9 mg/dL) per allele ( P =5.6×10 −49 ), which was >3× larger than the largest effect sizes seen with other common variants in other populations. Carriers of p.G116S had a 3.02-fold increased risk of hypercholesterolemia (95% confidence interval, 2.34–3.90; P =1.7×10 −17 ), but did not have classical familial hypercholesterolemia. In vitro, p.G116S showed 60% reduced ligand-binding activity compared with wild-type receptor. In contrast, p.R730W was associated with neither LDL cholesterol level nor altered in vitro activity. Conclusions—: LDLR p.G116S is thus unique: a common dysfunctional variant in Inuit whose large effect on LDL cholesterol may have public health implications. Abstract : Supplemental Digital Content is available in the text.